Rethinking Technology-Based Islamic Boarding School Education Management - Srie Faizah Lisnasari; Gemala Widiyarti; Jainab Jainab; Ulfah Sari Rezeki; Hasni Suciawati (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
The aim of this research is to look at the governance of technology-based Islamic education at the madrasah level in the city of Medan, namely Madrasah Ibtidaiyah Al Quba. The study of this research uses qualitative research methods. Methods of data collection using interviews, observation and documentation. Interviews were conducted with teachers and students. The results of the study show that governance at the Al Quba Ibtidaiyah madrasah level, Medan is a significant matter, because along with changing times, technology cannot be avoided, so that if there are madrasas that do not keep up with the times, they will be left behind by other schools. What's more, schools are currently the same as competition to get students, so technology is the main source for introducing schools to outsiders.